2016
DOI: 10.1111/agec.12228
|View full text |Cite
|
Sign up to set email alerts
|

Rice mountain: assessment of the Thai rice pledging program

Abstract: The Thai Government introduced a generous price support program for paddy rice in 2011. The policy terminated in mid 2014 with the dismissal of the democratically elected Prime Minister, Ms Yingluck Shinawatra. There is an interest in understanding the welfare effects of the policy given the ongoing civil suit put against the former Prime Minister and the large stocks that remain. This study therefore analyses the welfare effects of various Thai rice policy options using a 10-region, dynamic, stochastic, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Similarly, Thailand, through its Paddy Pledging Scheme, has occasionally sought to influence the price received by rice farmers for their crops, most notably in the post-2011 period, when rice farmers were paid 50% more than the market price. This resulted in a large accumulation of stocks and downward pressure on international prices before it ceased (Permani and Vanzetti, 2014;OECD, 2017-SEA).…”
Section: Various Input and Output Programmes Existmentioning
confidence: 99%
“…Similarly, Thailand, through its Paddy Pledging Scheme, has occasionally sought to influence the price received by rice farmers for their crops, most notably in the post-2011 period, when rice farmers were paid 50% more than the market price. This resulted in a large accumulation of stocks and downward pressure on international prices before it ceased (Permani and Vanzetti, 2014;OECD, 2017-SEA).…”
Section: Various Input and Output Programmes Existmentioning
confidence: 99%
“…The program was set up mainly for political purposes, rather than for farmers. Laiprakobsup [11], Permani and Vanzetti [14], and Attavanich [4], suggested that government should instead assist farmers in the long run, such as providing supports in terms of fertilizers, harvesting tools, rice seeds, warehouse and even providing low interest loan for farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the relative size of this type of expenditure suggests that these are not the main focus of policy in many countries. 7 On the consumer side, some countries have public distribution and public stocking regimes aimed at provide subsidised rice and in some instance also at stabilising market Stockholding policies are also seen on the exporter side, with Thailand at various points over time using government purchasing and stockholding policies as a means to influence producer incomes and influencing world prices (Permani and Vanzetti, 2014).…”
Section: Agricultural Policies In Southeast Asia: a Focus On Rice Andmentioning
confidence: 99%